The role of semen in sexual transmission of HIV: beyond a carrier for virus particles. - Sabatte, Juan Atilio (2011)
Unprotected sexual intercourse between discordant couples is by far the most frequent mode of HIV-1 (human immunodeficiency virus type 1) transmission being semen the main vector for HIV-1 dissemination worldwide. Semen is usually considered merely as a vehicle for HIV-1 transmission. In this review we discuss recent observations suggesting that beyond being a carrier for virus particles semen markedly influences the early events involved in sexual transmission of HIV through the mucosal barriers.